PENGARUH RETURN ON ASSET (ROA), EARNING PER SHARE (EPS), DIVIDEND PAYOUT RATIO (DPR ) DAN LEVERAGE TERHADAP RETURN SAHAM (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2009 – 2011) (Students' Journal of Economic and Management, 2014)
The purpose of this study is to examine and analyze the Effect Return on Assets , Earning Per Share , Dividend Payout Ratio , Leverage And Return Of Shares In The Manufacturing Company Listed on the Indonesia Stock Exchange study period from 2009 to 2011.The population of this study is manufacturing companies listed in Indonesia Stock Exchange in the period 2009 to 2011 . Research sampling technique using purposive sampling method 30 sampel.Analisis data used to answer the research hypotheses using multiple regression analysis , after the previous test data and the classical assumption of normality . In addition , this study also tested the fit of the model . The analytical tool used is the F test and the coefficient of determination .The results of this study indicate that the Earning Per Share and debt to total assets and a significant positive effect on stock returns , while Return on Assets Dividend Payout Ratio and no significant effect on stock returns . Keywords :Return on Assets , Earning Per Share , Dividend Payout Ratio , Leverage , and Stock Return